2021
DOI: 10.1021/acsphotonics.1c00287
|View full text |Cite
|
Sign up to set email alerts
|

2D Carrier Localization at the Wurtzite-Zincblende Interface in Novel Layered InP Nanomembranes

Abstract: The successful application of semiconductor nanostructures in devices has attracted intense interest in their carrier dynamics. Here an in-depth investigation of the carrier dynamics in novel layered InP nanomembranes with a large area of atomically sharp wurtzite-zincblende (WZ-ZB) interface is conducted for the first time by using various spectroscopic techniques. Two kinds of type II transitions in these nanomembranes are observed, which are from the ZB/WZ type II planar interface and stacking faultinduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 47 publications
7
10
0
Order By: Relevance
“…The position of this peak is at ≈920 nm at 1 mA of current injection, which is consistent with reported values. [49] Moreover, as the injected current increases, a blue shift in the peak is observed similar to that reported by Su et al confirming this peak originates from the interface of NW (WZ) and InP substrate (ZB). [49] Another possibility of this peak could be the mixed-phase structure in the NWs.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The position of this peak is at ≈920 nm at 1 mA of current injection, which is consistent with reported values. [49] Moreover, as the injected current increases, a blue shift in the peak is observed similar to that reported by Su et al confirming this peak originates from the interface of NW (WZ) and InP substrate (ZB). [49] Another possibility of this peak could be the mixed-phase structure in the NWs.…”
Section: Resultssupporting
confidence: 84%
“…[49] Moreover, as the injected current increases, a blue shift in the peak is observed similar to that reported by Su et al confirming this peak originates from the interface of NW (WZ) and InP substrate (ZB). [49] Another possibility of this peak could be the mixed-phase structure in the NWs. However, we rule out this case here as it has previously been reported that for the above-mentioned growth conditions, the NWs have a pure WZ phase.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…At low temperatures, the carriers are highly localized, and electronic transitions strongly are coupled to lattice vibrations. 38 The quantum dissipation effect of the phonon bath leads to the asymmetric and broad emission band, which are consistent with the sharp rise at the blue edge and long tail at the red edge observed by PL. Thus, photons with a wide range of energies possess an indistinguishable dynamic feature, verifying the phenomenon in TRPL (Figure 2c,d).…”
Section: ■ Results and Discussionsupporting
confidence: 80%